2012
DOI: 10.1371/journal.pone.0038986
|View full text |Cite
|
Sign up to set email alerts
|

Increased Asymmetric and Multi-Daughter Cell Division in Mechanically Confined Microenvironments

Abstract: As the microenvironment of a cell changes, associated mechanical cues may lead to changes in biochemical signaling and inherently mechanical processes such as mitosis. Here we explore the effects of confined mechanical environments on cellular responses during mitosis. Previously, effects of mechanical confinement have been difficult to optically observe in three-dimensional and in vivo systems. To address this challenge, we present a novel microfluidic perfusion culture system that allows controllable variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 24 publications
8
76
0
Order By: Relevance
“…By applying a range of feedback-controlled confinement forces, we confirmed several of their observations including spindle widening and flattening (28,29), accelerated mitotic progression with small deformations (23), asymmetric spindle positioning (10), and delayed mitotic progression due to ectopic spindle function below a critical height (2). We identified several force regimes according to the cell response: small forces (∼5 nN) that accelerate mitotic progression, intermediate forces (50-100 nN) where increased intracellular pressure was related to resistance to confinement, and, finally, yield forces (>100 nN) where mitotic progression was inhibited by mechanical perturbation of spindle geometry.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…By applying a range of feedback-controlled confinement forces, we confirmed several of their observations including spindle widening and flattening (28,29), accelerated mitotic progression with small deformations (23), asymmetric spindle positioning (10), and delayed mitotic progression due to ectopic spindle function below a critical height (2). We identified several force regimes according to the cell response: small forces (∼5 nN) that accelerate mitotic progression, intermediate forces (50-100 nN) where increased intracellular pressure was related to resistance to confinement, and, finally, yield forces (>100 nN) where mitotic progression was inhibited by mechanical perturbation of spindle geometry.…”
Section: Discussionsupporting
confidence: 56%
“…In mitosis, cells generate actomyosindependent (1) intracellular pressure to round up and optimize geometry for proper function of the mitotic spindle, the machinery that organizes and segregates chromosomes (2,9,10,22). Restricting cell rounding height below 5-8 μm with microfabricated PDMS chambers perturbs mitotic progression in several cell types (2, 10), but the forces that cells can withstand remain unquantified.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have described that actin and actin-binding proteins function at the heart of the spindle [61] and several groups have shown defects in spindle formation following perturbations of the actin cytoskeleton [62,63]. Such observations suggested the possibility that the actin cytoskeleton might play a direct role in spindle formation itself [61,64,65]. During mitosis, accurate chromosome segregation requires precise coordination of the microtubule-based spindle and the actin-based cell cortex.…”
Section: Discussionmentioning
confidence: 99%
“…293 daughter cells resulting from the rare multipolar divisions and incomplete cytokinesis, which are accompanied by an unequal segregation of chromosomes (Gisselsson et al, 2008(Gisselsson et al, , 2010, are presumably unviable undergoing mitotic cell death, cell-cycle arrest or senescence as it was demonstrated for other cell lines (Ganem et al, 2009;Marthiens et al, 2012;Stewénius et al, 2005). Nevertheless, it was observed that a few karyotypes of multipolar mitosis daughter cells could survive, underwent clonal evolution and expanded in culture (Tse et al, 2012;Yang et al, 2012 and refs herein). Thereby, the rare multipolar mitoses can potentially contribute to karyotype diversification of 293 cells.…”
Section: Introductionmentioning
confidence: 97%